I solved a physics problem and I got this equation, but I don't know how to proceed. Could you solve for $x (t)$ this equation: $x \ddot {x} + {\dot {x}}^2=0$

  • 1
    $\begingroup$ $$x(t)=c_2 \sqrt{2 t-c_1}$$ $\endgroup$ Oct 13 '17 at 10:23
  • $\begingroup$ Was that a guess or is there an analytical way to do this. $\endgroup$
    – Sonal_sqrt
    Oct 13 '17 at 10:24
  • $\begingroup$ Wolfram alpha and the textbook solution give $x(t)= c_2 \sqrt {c_1 + 2t}$ $\endgroup$
    – Flaffo
    Oct 13 '17 at 10:27
  • $\begingroup$ Divide by $x$ and also by $x'$. Then it is easy to integrate. $\endgroup$
    – user121049
    Oct 13 '17 at 10:32

$$x\ddot{x} + \dot{x}^2=\frac{d}{dt}(x\dot{x})=0\\ x\frac{dx}{dt}=c_1\\ \int xdx=\int c_1 dt\\ \frac{x^2}{2}=c_1t+c_2\\ x=\sqrt{2c_1t+c_2}$$ which may be rewritten as $$x=c_1\sqrt{2t+c_2}$$


$(xx')'=xx''+x'^2=0$ and $2xx'=2C$ then $(x^2)'=2C$ so $x^2=2Ct+D$.


Note that $x'' = \dfrac{\mathrm dx'}{\mathrm dt} = \dfrac{\mathrm dx'}{\mathrm dx} \dfrac{\mathrm dx}{\mathrm dt} = \dfrac{\mathrm dx'}{\mathrm dx} x'$.

Therefore: $$x \dfrac{\mathrm dx'}{\mathrm dx} x' + (x')^2 = 0$$

Then: $$x \dfrac{\mathrm d(x')^2}{\mathrm dx} + 2(x')^2 = 0$$

Let $v=(x')^2$: $$x \dfrac{\mathrm dv}{\mathrm dx} + 2v = 0$$

Separating variables: $$\dfrac1{-2v} \dfrac{\mathrm dv}{\mathrm dx} = \dfrac1x$$

Integrating both sides: $$-\dfrac12\ln v = \ln x + C$$

Therefore: $$v = k_0 x^{-2}$$

Substituting the definition of $v$: $$\dfrac{\mathrm dx}{\mathrm dt} = k_1 x^{-1}$$

Taking reciprocal of both sides: $$\dfrac{\mathrm dt}{\mathrm dx} = k_2 x$$

Integrating both sides: $$t=Ax^2+B$$

  • $\begingroup$ @samjoe solved. $\endgroup$
    – Kenny Lau
    Oct 13 '17 at 10:53

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.